Copper surface organic acid uniform roughening method
By preparing a mixed solution containing copper chloride, organic acid, organic amine, polycaticidal compound and iodine ion, the copper surface is evenly rough and rough, solving the problem of copper layer in the existing technology. The high efficiency and even roughness of the copper layer and the reliable connection with organic materials.
Patent Information
- Application Number
- CN202411313623.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-28
AI Technical Summary
The existing organic acid-copper chloride-organic amine additives are susceptible to impurities to contaminate the copper layer, causing the copper layer to bloom and reduce the reliability of the copper layer to connect with the organic material.
By preparing the mixed solution of copper chlorine, organic acid and organic acid, organic acid, organic amine, polycaticidal compound, and iodine ion, the copper surface is evenly rough and rough to improve the impurities tolerance and improve the rough effect of the copper layer.
The height and even roughness of the copper layer is realized, the proportion of the "fake" is reduced, the connection reliability of the copper layer and the organic material is improved, and the problem of the flowers of the copper layer is avoided.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper surface organic acid uniform roughening, in particular to a copper surface organic acid uniform roughening method. Background Art
[0002] In the modern printed circuit board manufacturing process, a variety of copper layer and organic material connection processes are involved to obtain high reliability and high yield products. For example, when using organic photosensitive materials such as dry film or wet film to cover the copper layer and subsequently forming the required circuit pattern, the connection between the dry film or wet film and the copper layer is involved. The higher the bonding force between the two, the higher the product yield. For another example, when using organic photosensitive or thermal sensitive resins or inks to plug the buried holes in the inner layer, the connection between the plugging resin or ink and the copper layer is involved. In addition, the ink production process on the surface of the printed circuit board involves the connection between the ink and the copper layer.
[0003] In order to improve the connection reliability between the above copper layer and the organic material, the general method in the industry is to use a mixed solution of acid and oxidant to roughen the copper layer. This method of roughening the copper surface effectively increases the specific surface area of copper, thereby improving the bonding strength between the copper layer surface and the organic material. A typical representative of this type of treatment solution is an organic acid-copper chloride mixed solution, that is, an ultra-roughened micro-etching solution. Without adding other compounds, the bonding strength between the copper layer and the organic material obtained by the organic acid-copper chloride treatment solution is usually insufficient, which is manifested as easy oxidation when placed at room temperature, resulting in low product yield. By using the well-known organic acid-copper chloride treatment solution additives (mainly organic amines and their derivatives, such as polyethyleneimine with different degrees of polymerization), the connection reliability between the copper layer and the organic material can be significantly improved. However, the roughening ability of the copper layer by organic amine additives is very easily affected by impurity contamination. When the board is not clean enough, the surface of the copper layer is flowery after being treated with the organic acid-copper chloride-organic amine mixed solution, which reduces the reliability of the connection between the copper layer and the organic material.
[0004] In order to solve the above problems, the present invention provides a method for uniformly roughening a copper surface with an organic acid, which improves the tolerance of the organic acid-copper chloride-organic amine roughening system to impurities and improves the problem of copper layer blooming. Summary of the invention
[0005] The object of the present invention is to provide a method for uniformly roughening a copper surface with organic acid, so as to solve the problem in the above-mentioned background technology that the roughening ability of the copper layer by copper chloride-organic acid-organic amine additives is easily contaminated by impurities.
[0006] To achieve the above object, the present invention provides the following technical solution: a method for uniformly roughening a copper surface with organic acid, comprising the following preparation steps:
[0007] Step 1, preparing oxidant copper chloride, organic acid and organic acid salt, organic amine, polyhydroxy compound and iodide ion, at which the ratio of polyhydroxy compound to iodide ion is (10-500):1, and the required roughening solution is obtained;
[0008] Step 2: Heat the roughening solution obtained in step 1 to 35°C in a water bath, then immerse the FR-4 copper clad laminate sample with a surface copper thickness of 35 μm into it, continuously etch for 60 seconds, then take out the sample, clean it, and dry it. The test piece obtains a uniformly rough reddish-brown appearance.
[0009] Preferably, in step 1, the oxidant cupric chloride is a reaction product of copper and chlorine or a reaction product of copper oxide and hydrochloric acid, and the content of the oxidant cupric chloride in the roughening solution is preferably 0.5%-15%.
[0010] Preferably, in step one, the organic acid and organic acid salt include but are not limited to formic acid, acetic acid, propionic acid, butyric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, maleic acid, acrylic acid, lactic acid, citric acid, sodium formate, sodium acetate, sodium propionate, sodium butyrate, sodium oxalate, sodium malonate, sodium succinate, sodium glutarate, sodium maleate, sodium acrylate, sodium lactate or sodium citrate, and the content of the organic acid and organic acid salt in the roughening liquid is preferably 0.1%-35%.
[0011] Preferably, in step 1, the organic amine is a cationic polymer including but not limited to polyethyleneimine, polydimethyldiallyl ammonium chloride, cationic polyacrylamide, polyvinylpyrrolidone or polyquaternary ammonium salt, and the content of the organic amine in the roughening liquid is preferably 0.01ppm-10000ppm.
[0012] Preferably, in step 1, the polyhydroxy compound includes but is not limited to polyols and their polymers, including ethylene glycol, propylene glycol, butylene glycol, diethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polybutylene glycol, glycerol and its derivatives, sorbitol or mannitol, and the content of the polyhydroxy compound in the roughening liquid is preferably 0.01ppm-1000ppm.
[0013] Preferably, the mass ratio of the polyhydroxy compound to the iodide ion is more preferably (20-200):1.
[0014] Preferably, in step 1, the iodide ions are derived from sodium iodide, potassium iodide or hydroiodic acid.
[0015] Compared with the prior art, the present invention has the following beneficial effects:
[0016] The organic acid roughening solution of the present invention is used to treat copper or copper alloy to form a highly uniform roughening appearance, and after the conductive pattern is formed on the plate, the proportion of "false points" is reduced when the plate is subjected to automatic optical inspection (AOI). DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0018] The present invention provides a method for uniformly roughening a copper surface using an organic acid, comprising the following preparation steps:
[0019] Step 1, preparing oxidant copper chloride, organic acid and organic acid salt, organic amine, polyhydroxy compound and iodide ion, at which the ratio of polyhydroxy compound to iodide ion is (10-500):1, and the required roughening solution is obtained;
[0020] Step 2: Heat the roughening solution obtained in step 1 to 35°C in a water bath, then immerse the FR-4 copper clad laminate sample with a surface copper thickness of 35 μm into it, continuously etch for 60 seconds, then take out the sample, clean it, and dry it. The test piece obtains a uniformly rough reddish-brown appearance.
[0021] The oxidant cupric chloride is a reaction product of copper and chlorine or a reaction product of copper oxide and hydrochloric acid. The content of the oxidant cupric chloride in the roughening solution is preferably 0.5%-15%, more preferably 1%-10%. When it is lower than 0.5%, the oxidizing ability is insufficient to form a proper rough morphology on the copper surface. When it is higher than 15%, the oxidizing ability is too high, which may cause excessive etching of the copper layer in the hole and damage the conductive property of the hole. In addition, excessive copper ions may cause precipitation in the roughening solution.
[0022] The organic acid and organic acid salt include, but are not limited to, formic acid, acetic acid, propionic acid, butyric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, maleic acid, acrylic acid, lactic acid, citric acid, sodium formate, sodium acetate, sodium propionate, sodium butyrate, sodium oxalate, sodium malonate, sodium succinate, sodium glutarate, sodium maleate, sodium acrylate, sodium lactate or sodium citrate. The content of the organic acid and organic acid salt in the roughening solution is preferably 0.1%-35%, more preferably 1%-30%. When the content is lower than 0.1%, the pH value of the roughening solution fluctuates greatly, the roughening rate is unstable, and the copper ions dissolved during the roughening cannot be fully dissolved. When the content is higher than 35%, the copper layer will be locally passivated or oxidized, and a uniformly roughened surface cannot be obtained.
[0023] The organic amine is a cationic polymer including but not limited to polyethyleneimine, polydimethyldiallyl ammonium chloride, cationic polyacrylamide, polyvinylpyrrolidone or polyquaternary ammonium salt. The content of the organic amine in the roughening solution is preferably 0.01ppm-10000ppm, more preferably 0.1ppm-1000ppm. When it is lower than 0.01ppm, the plate cannot form a uniformly rough appearance. When it is higher than 10000ppm, the roughening rate decreases, and the copper layer cannot even be roughened.
[0024] The polyols include, but are not limited to, polyols and polymers thereof, including ethylene glycol, propylene glycol, butylene glycol, diethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polybutylene glycol, glycerol and derivatives thereof, sorbitol or mannitol. The content of the polyols in the roughening solution is preferably 0.01ppm-1000ppm, more preferably 0.1ppm-500ppm. When the content is lower than 0.01ppm, the plate cannot form a uniformly rough appearance. When the content is higher than 1000ppm, the roughening rate decreases, and the copper layer cannot even be roughened. The mass ratio of the polyol to the iodide ion is more preferably (20-200):1. When the content of the polyol is higher, the color of the copper becomes lighter after roughening, which means that the roughness decreases. When the content of the iodide ion is higher, the roughening rate is unstable.
[0025] Iodide ions are derived from sodium iodide, potassium iodide or hydroiodic acid.
[0026] Embodiment 1:
[0027] 5%wt of cupric chloride dihydrate, 8%wt of formic acid, 5%wt of sodium formate, 5ppm of polyquaternium-11, 7.5ppm of diethylene glycol, and 0.1ppm of potassium iodide were prepared, and the ratio of diethylene glycol to iodide ion was 98:1, which was the roughening solution of the present invention. The roughening solution was heated to 35°C in a water bath, and then a FR-4 copper-clad laminate sample with a surface copper thickness of 35μm was immersed therein, and the sample was continuously etched for 60 seconds, and then the sample was taken out, cleaned, and dried, and the test piece obtained a uniformly rough reddish-brown appearance.
[0028] Embodiment 2:
[0029] 5%wt of cupric chloride dihydrate, 8%wt of formic acid, 5%wt of sodium formate, 5ppm of polyquaternium-7, 7.5ppm of diethylene glycol, and 0.1ppm of potassium iodide were prepared, and the ratio of diethylene glycol to iodide ion was 98:1, which was the roughening solution of the present invention. The roughening solution was heated to 35°C in a water bath, and then a FR-4 copper-clad laminate sample with a surface copper thickness of 35μm was immersed therein, and the sample was continuously etched for 60 seconds, and then the sample was taken out, cleaned, and dried, and the test piece obtained a uniformly rough reddish-brown appearance.
[0030] Embodiment three:
[0031] 5%wt of cupric chloride dihydrate, 8%wt of formic acid, 5%wt of sodium formate, 5ppm of polyethyleneimine 70000, 7.5ppm of diethylene glycol, and 0.1ppm of potassium iodide were prepared, and the ratio of diethylene glycol to iodide ion was 98:1, which was the roughening solution of the present invention. The roughening solution was heated to 35°C in a water bath, and then a FR-4 copper-clad laminate sample with a surface copper thickness of 35μm was immersed therein, and the sample was continuously etched for 60 seconds, and then the sample was taken out, cleaned, and dried, and the test piece obtained a uniformly rough dark brown appearance.
[0032] Embodiment 4:
[0033] 5%wt of cupric chloride dihydrate, 8%wt of formic acid, 5%wt of sodium formate, 5ppm of polyquaternium-11, 7.5ppm of diethylene glycol, and 0.2ppm of potassium iodide were prepared, and the ratio of diethylene glycol to iodide ion was 49:1, which was the roughening solution of the present invention. The roughening solution was heated to 35°C in a water bath, and then a FR-4 copper-clad laminate sample with a surface copper thickness of 35μm was immersed therein, and the sample was continuously etched for 60 seconds, and then the sample was taken out, cleaned, and dried, and the test piece obtained a uniformly rough light reddish brown appearance.
[0034] Embodiment five:
[0035] 5%wt of cupric chloride dihydrate, 8%wt of formic acid, 5%wt of sodium formate, 5ppm of polyquaternium-7, 11.5ppm of diethylene glycol, and 0.1ppm of potassium iodide were prepared, and the ratio of diethylene glycol to iodide ion was 150:1, which was the roughening solution of the present invention. The roughening solution was heated to 35°C in a water bath, and then a FR-4 copper-clad laminate sample with a surface copper thickness of 35μm was immersed therein, and the sample was continuously etched for 60 seconds, and then the sample was taken out, cleaned, and dried, and the test piece obtained a uniformly rough reddish-brown appearance.
[0036] Comparative Example 1:
[0037] 5%wt cupric chloride dihydrate, 8%wt formic acid, 5%wt sodium formate, 5ppm polyquaternium-7, 11.5ppm diethylene glycol were prepared without adding iodide. The above roughening solution was heated to 35°C in a water bath, and then the FR-4 copper clad laminate sample with a surface copper thickness of 35μm was immersed in it, and the sample was continuously etched for 60 seconds, and then the sample was taken out, cleaned, and dried. The appearance of the test piece was flowery and uneven.
[0038] Comparative Example 2:
[0039] 5%wt cupric chloride dihydrate, 8%wt formic acid, 5%wt sodium formate, 5ppm polyquaternium-7, 0.1ppm potassium iodide were prepared without adding polyol. The above roughening solution was heated to 35°C in a water bath, and then a FR-4 copper-clad laminate sample with a surface copper thickness of 35μm was immersed in it, and the sample was continuously etched for 60 seconds, and then the sample was taken out, cleaned, and dried. The appearance was flowery and uneven.
[0040] Comparative Example 3:
[0041] 5%wt of cupric chloride dihydrate, 8%wt of formic acid, 5%wt of sodium formate, 5ppm of polyquaternium-7, 11.5ppm of diethylene glycol, and 0.025ppm of potassium iodide are prepared, and the ratio of diethylene glycol to iodide ion is 600:1, that is, the roughening solution of the present invention. The roughening solution is heated to 35°C in a water bath, and then a FR-4 copper-clad laminate sample with a surface copper thickness of 35μm is immersed therein, and the sample is continuously etched for 60 seconds, and then the sample is taken out, cleaned, and dried, and the appearance is slightly flowery and uneven.
[0042] Comparative Example 4:
[0043] 5%wt of cupric chloride dihydrate, 8%wt of formic acid, 5%wt of sodium formate, 5ppm of polyquaternium-7, 7.5ppm of diethylene glycol, and 1.5ppm of potassium iodide are prepared, and the ratio of diethylene glycol to iodide ion is 5:1, that is, the roughening solution of the present invention. The above roughening solution is heated to 35°C in a water bath, and then a FR-4 copper-clad laminate sample with a surface copper thickness of 35μm is immersed therein, and the sample is continuously bitten for 60 seconds, and then the sample is taken out, cleaned, and dried, and the appearance is light red, and the roughening rate is significantly reduced.
[0044] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for uniformly roughening a copper surface using organic acid, characterized in that: The method comprises the following preparation steps: Step 1, preparing oxidant copper chloride, organic acid and organic acid salt, organic amine, polyhydroxy compound and iodide ion, at which the ratio of polyhydroxy compound to iodide ion is (10-500):1, and the required roughening solution is obtained; Step 2: Heat the roughening solution obtained in step 1 to 35°C in a water bath, and then immerse the FR-4 copper clad laminate sample with a surface copper thickness of 35 μm into it. The etching was continued for 60 seconds, and then the sample was taken out, cleaned and dried, and the test piece obtained a uniform rough reddish brown appearance.
2. The method for uniformly roughening a copper surface with organic acid according to claim 1, characterized in that: In the step 1, the oxidant cupric chloride is a reaction product of copper and chlorine or a reaction product of copper oxide and hydrochloric acid, and the content of the oxidant cupric chloride in the roughening solution is preferably 0.5%-15%.
3. The method for uniformly roughening a copper surface with organic acid according to claim 1, characterized in that: In the step 1, the organic acid and organic acid salt include but are not limited to formic acid, acetic acid, propionic acid, butyric acid, oxalic acid, malonic acid, succinic acid, glutaric acid, maleic acid, acrylic acid, lactic acid, citric acid, sodium formate, sodium acetate, sodium propionate, sodium butyrate, sodium oxalate, sodium malonate, sodium succinate, sodium glutarate, sodium maleate, sodium acrylate, sodium lactate or sodium citrate, and the content of the organic acid and organic acid salt in the roughening liquid is preferably 0.1%-35%.
4. The method for uniformly roughening a copper surface with organic acid according to claim 1, characterized in that: In the step 1, the organic amine is a cationic polymer including but not limited to polyethyleneimine, polydimethyldiallyl ammonium chloride, cationic polyacrylamide, polyvinylpyrrolidone or polyquaternary ammonium salt, and the content of the organic amine in the roughening liquid is preferably 0.01ppm-10000ppm.
5. The method for uniformly roughening a copper surface with organic acid according to claim 1, characterized in that: In the step 1, the polyhydroxy compound includes but is not limited to polyols and polymers thereof, including ethylene glycol, propylene glycol, butylene glycol, diethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polybutylene glycol, glycerol and derivatives thereof, sorbitol or mannitol, and the content of the polyhydroxy compound in the roughening liquid is preferably 0.01ppm-1000ppm.
6. The method for uniformly roughening a copper surface with organic acid according to claim 1, characterized in that: The mass ratio of the polyhydroxy compound to the iodide ion is more preferably (20-200):
1.
7. The method for uniformly roughening a copper surface with organic acid according to claim 1, characterized in that: In the step 1, the iodide ions are derived from sodium iodide, potassium iodide or hydroiodic acid.